Evaluation of the efficacy of sticky bone and concentrated growth factor membrane along with a coronally advanced flap as compared to coronally advanced flap alone in the treatment of Miller's Class I and Class II gingival recession defects - Dipika Mitra; Shazneen Kandawalla; Priyanka Potdar; Shruti Patil; Amruta Naniwadekar; Gaurav Shetty (Wolters Kluwer Medknow Publications, 2022)
Context: Gingival recessions are commonly seen in the dentally cognizant population as well as those with limited access to dental attention. When root coverage is planned, the ultimate goal is to obtain complete root coverage, thus restoring the lost gingival unit covering the root. Aims: To determine the efficacy of sticky bone and concentrated growth factor (CGF) membrane along with a coronally advanced flap (CAF) as compared to CAF alone in treating Miller's Class I and Class II gingival recessions (Cairo RT1). Settings and Design: The current study was a randomized double-blind controlled trial on 15 subjects using a split-mouth design. Materials and Methods: Fifteen subjects who were systemically healthy and had recession sites (30 sites) were randomly assigned to two groups: Group A (test group = CAF + CGF + sticky bone) and Group B (control group = CAF alone). Clinical outcome was assessed with parameters such as recession depth, recession width, keratinized gingival width, gingival mucosal thickness, and relative attachment level (RAL), and these were assessed at baseline and 1, 3, and 6 months. Results: A distinct improvement was observed in the depth and width of recession, RAL, keratinized gingival width, and mucosal thickness of the gingiva in the two groups from baseline to 6 months. Statistical significance was not seen on intergroup comparisons. Conclusions: Thus, clinical outcomes revealed noticeable improvement for both the groups. However, statistically, the efficacy of CGF and sticky bone was not perceived to be superior to that of CAF alone.